Towards sustainable development : Coupling green marketing strategies and consumer perceptions in addressing greenwashing - Rahman, Saleem ur; Nguyen-Viet, Bang (Wiley, 2023)
To understand how consumers perceive greenwashing, this study examines the impact of green advertising receptivity (GAR), non-deception (ND), green brand image (GBI) and transparency (TR) on green brand trust (GBT) and subsequently the impact of GBT on consumers' purchasing intentions (PI). We also consider the mediation role of GBT between the relationship of the independent variables (GAR, ND, GBI and TR) and the dependent variable (PI). At the same time, we examine the moderating impact of ND on the GAR and GBT and of TR on the GBI and GBT relationship. Using the Stimulus–Organism–Response (SOR) framework, we test a number of hypotheses. A survey-based questionnaire was utilized to gather the data from Vietnamese respondents (n = 262). We analysed the data using the partial least squares (PLS) method, which is a structural equation modelling (SEM) technique, with the assistance of the SmartPLS computer program 3.0. The data results show that GAR and GBI positively influence GBT, but the influence of ND and TR on GBT is insignificant. Again, the data show that GBT has a positive influence on PI, and as a mediator variable, it facilitates GAR, GBI and PI, but not the link between ND, TR and PI. A significant interaction effect of ND demonstrates that it strengthens the GAR-GBT relationship. However, the TR has no impact on the GBI–GBT relationship. The findings of this study provide insights into the theory and the essential managerial implications for successfully managing the implementation of green marketing strategies.
Keywords: green advertising; green brand image; green brand trust; greenwashing; purchase intention; fi=Markkinointi|en=Marketing|